Prinsip-Prinsip Dan Kaidah Transaksi Dalam Ekonomi Syari’ah - Syaripudin, Enceng Iip; Konkon Furkony , Deni; Maulin, Merry; Bisri, Hasan (STAI Al Musaddadiyah Garut, 2022)
Islam as a living system (Way Of Live), humans are caliphs on earth and Islam views that the earth with everything in it is a mandate from Allah SWT to the caliph to be used as well as possible for the common welfare. In the activities of worship that Goer Mahdoh (muamalah), humans are given the right to be creative, creative and carry out any activity that can provide good for themselves and the wider community, as long as they do not violate prohibitions, and in accordance with the economic principles of Shari'ah in order to obtain the welfare of the world and the Hereafter The objectives to be achieved in this study are: 1) What is meant by the Principles and Rules of Transactions in the Sharia Economy. 3). To know how the principles and rules of transactions in the Shari'ah economy. The research method used in this study is the library research method or book survey. The library research method is a research method that. Keywords: Prinsif, rules, Transactions, Islamic economics